Entropy is better related to unification than to order. (January 2023) - Cottam, Ron; Vounckx, Roger
Abstract: There are difficulties related to the classical establishment of entropy. It is conventionally viewed as the inverse of order in a system, or more precisely as a quantification of the number of possible systemic microstate reorganisations. This should attribute the related energy to a spectrum of possibilities, from the conventionally 'expected order at one end to a different unexpected order at the other, with disorder between the two', rather than the conventional 'order at one end to disorder at the other'. We propose that the resolution of this dichotomy lies in relating entropy to system unification, in place of simplistic order, which in any case is unfathomable in a complex organisationally multi-levelled organism. We conclude by questioning the entropic place of the brain in the Universe.